ANALISIS LOKASI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO LARIS DI SITUBONDO - Fitrianingsi, Ayu; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing is one of the main activities carried out by companies in maintaining their marketing survival, developing to make a profit. This study aims to analyze the location and quality of service to consumer loyalty with customer satisfaction as an intervening variable. The population in this study was consumers of TokoLarisSitubondo. The sampling technique was determined by quota sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that location has a significant positive effect on customer satisfaction, service quality has a significant positive effect on customer satisfaction, location has a significant positive effect on customer loyalty, service quality has a significant positive but insignificant effect on customer loyalty, customer satisfaction has a significant positive effect on customer loyalty, location on customer loyalty through customer satisfaction has a significant positive effect, service quality on customer loyalty through customer satisfaction has a significant positive effect.